10.4k views
5 votes
The sum of two polynomials is 10a2b2 – 8a2b + 6ab2 – 4ab + 2. If one addend is –5a2b2 + 12a2b – 5, what is the other addend?

15a2b2 – 20a2b + 6ab2 – 4ab + 7
5a2b2 – 20a2b2 + 7
5a2b2 + 4a2b2 + 6ab – 4ab – 3
–15a2b2 + 20a2b2 – 6ab + 4ab – 7

2 Answers

3 votes

Answer: The correct option is (A)
15a^2b^2-20a^2b+6ab^2-4ab+7.

Step-by-step explanation: Given that the sum of two polynomials is
(10a^2b^2-8a^2b+6ab^2-4ab+2) and one addend is
(-5a^2b^2+12a^2b-5).

We are to find the other addend.

Let P(x) be the other addend.

Then, according to the given information, we must have


-5a^2b^2+12a^2b-5+P(x)=10a^2b^2-8a^2b+6ab^2-4ab+2\\\\\Rightarrow P(x)=(10a^2b^2-8a^2b+6ab^2-4ab+2)-(-5a^2b^2+12a^2b-5)\\\\\Rightarrow P(x)=10a^2b^2-8a^2b+6ab^2-4ab+2+5a^2b^2-12a^2b+5\\\\\Rightarrow P(x)=15a^2b^2-20a^2b+6ab^2-4ab+7.

Thus, the other addend is
15a^2b^2-20a^2b+6ab^2-4ab+7.

Option (A) is CORRECT.

User Mugetsu
by
6.0k points
4 votes

Answer:


15a^2b^2-20a^2b+6ab^2-4ab+7

Explanation:

The sum of two polynomials is


10a^2b^2-8a^2b+6ab^2-4ab+2

First addend is


-5a^2b^2+12a^2b-5

Second addend x.

Hence,


x+(-5a^2b^2+12a^2b-5)=10a^2b^2-8a^2b+6ab^2-4ab+2\\ \\x=10a^2b^2-8a^2b+6ab^2-4ab+2-(-5a^2b^2+12a^2b-5)=\\ \\=10a^2b^2-8a^2b+6ab^2-4ab+2+5a^2b^2-12a^2b+5=\\ \\=(10a^2b^2+5a^2b^2)+(-8a^2b-12a^2b)+6ab^2-4ab+(2+5)=\\ \\=15a^2b^2-20a^2b+6ab^2-4ab+7

User Robert Slaney
by
5.7k points